Opera omnia Desiderii Erasmi Roterodami: recognita et adnotatione critica instrvcta notisqve illvstrata / Ordo 2, Tomus 7 Adagiorvm Chilias Qvarta (pars prior) / ed. R. Hoven. Centuriam quintam ed. C. Lauvergnat-Gagnière - Erasmus, Desiderius (Opera omnia Desiderii Erasmi Roterodami recognita et adnotatione critica instructa notisque illustrata, 1999)
The seventh volume of the Adagia (Proverbs) of the Amsterdam edition of the Latin texts of Erasmus gives an introduction in French and a critical edition of the Latin text of the first half of the fourth thousand Adages. The text is accompanied by notes in French that trace Erasmus' sources and give linguistic, historical, philological and, where appropriate, theological background information which elucidates the text and Erasmus' way of working. (Verlagsinformation)